Auxin–cytokinin interplay shapes root functionality under low-temperature stress. (April 2023) - Tiwari, Manish; Kumar, Ritesh; Subramanian, Senthil; Doherty, Colleen J.; Jagadish, S.V. Krishna
Highlights: A healthy overall plant stature indispensably requires a firm base, and the root system must therefore be tolerant to low-temperature stress. The root system architecture is modulated by low-temperature stress, thereby affecting water and nutrient absorption. Phytohormone auxin and cytokinin signaling directly or indirectly regulate gravitropic response and root development during low-temperature stress. In addition, protective mechanisms during low-temperature stress-induced DNA damage in root stem cells involves auxin and cytokinin crosstalk. An interplay between auxin and cytokinin signaling in root tissue during low-temperature stress involving the activation or suppression of each other's signaling and transport cues, such as PIN proteins and the two-component system, determines the fate of root architecture and function. Abstract: Low-temperature stress alters root system architecture. In particular, changes in the levels and response to auxin and cytokinin determine the fate of root architecture and function under stress because of their vital roles in regulating root cell division, differentiation, and elongation. An intricate nexus of genes encoding components of auxin and cytokinin biosynthesis, signaling, and transport components operate to counteract stress and facilitate optimum development. We review the role of auxin transport and signaling and its regulation by cytokinin during root development and stem cell maintenance under low-temperature stress. We highlight intricate mechanisms operating in root stem cells to minimize DNA damage by altering phytohormone levels, and discuss a working model for cytokinin in low-temperatures stress response.